SOSIALISASI PEMANFAATAN SMARTPHONE DALAM PEMBELAJARAN DI KELAS UNTUK SISWA KELAS IV SDN MENGGARE KAB. PONOROGO - Styo Mahendra Wasito Aji; Mujahidin Farid; Heri Setiawan (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
The rapid technological advancements of the 21st century necessitate a transformation of smartphone usage from entertainment tools into productive educational media at the elementary school level. This community service program aimed to enhance digital literacy and ethical smartphone use among fourth-grade students at SDN Menggare, Ponorogo. The activity was conducted by a collaborative team of lecturers from the Elementary School Teacher Education (PGSD) departments of Surabaya State University and Mataram University, involving 17 students as participants. The methods employed included material presentations, demonstrations of educational features, and hands-on experience in utilizing smartphones for classroom learning. The impact of the program was measured using pre-socialization and post-socialization questionnaires consisting of 10 items. The results showed a significant increase in student understanding, with the average score rising from 48.5 to 90. Students are now able to identify digital learning features and are committed to using devices wisely. It is concluded that direct practice methods are effective in shifting students' mindsets toward productive technology integration. Continuous guidance from both teachers and parents is highly recommended to support students' academic achievement.